The Recent record of the Phalakron Plain Plushblue Flos apidanus phalakron (Lepidoptera: Lycaenidae) in South Sumatra after 91 years break - Muhammad Iqbal; Andes Syahputra; Arum Setiawan; Indra Yustian (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2020)
An individual of Phalakron Plain Plushblue Flos apidanus phalakron was observed and phtographed on 17 March 2020 at campus Sriwijaya University, Indralaya, South Sumatra province. In South Sumatra, this butterfly only known from a historical record in 1929. The recent observation of Flos apidanus phalakron in Indralaya represent a new record for South Sumatra province after 91 years break.